Mismatch of harvesting tool dimensions with hand parameters among oil palm workers in Johor - Mohd Yusoff, Irwan Syah; Mohd Tamrin, Shamsul Bahri; Mat Said, Aini; I., Mohd Afiq (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
A cross-sectional study was done among 273 oil palm workers who use harvesting tool when working. The objective of this study is to determine the mismatch of harvesting tool dimensions with anthropometric parameters. Purposive sampling method was used to recruit respondents based on the inclusive criteria such as male worker, age between 18 to 49 years old and working using harvesting tool. 273 male harvesters were selected in this study. A set of questionnaire consist of 3 parts, social demographic and background information, selected dimensions of tool and selected anthropometric data of worker’s was administered by interviewing the workers. SECA body meter was used to measure the stature of respondent to match with the length of handle. Diameter of handle was matched with internal grip diameter of workers measured using cone and measuring tape. All measurements were recorded in centimeter (cm). Sociodemographic data was analyzed by using descriptive analysis. Descriptive analysis was used to determine the mismatch between harvesting tool dimensions with anthropometric parameters. The results show that means for stature was 162.33 cm and 4.88 cm for internal grip diameter. For harvesting tool dimensions, mean for length of handle was 183.30 cm and the diameter of handle was constant, the mean was 2.80 cm. For mismatch it can divided as low mismatch, matching and high mismatch. Matching is the value that lies between the ranges of 80% to 99%. There was high mismatch of length of handle with stature (94.8%) and circumference of handle with internal grip diameter (100%). There was high mismatch of current harvesting tool dimensions with anthropometric parameters. The study showed that the proposed dimensions of harvesting tool have a low mismatch with selected anthropometric parameters.